Rothmund-Thomson Syndrome: A 13-Year Follow-Up - Guillermo Antonio Guerrero-González; Sylvia Aideé Martínez-Cabriales; Aideé Alejandra Hernández-Juárez; José de Jesús Lugo-Trampe; Nelly Alejandra Espinoza-González; Minerva Gómez-Flores; Jorge Ocampo-Candiani (Karger Publishers, 2014)
Rothmund-Thomson syndrome (RTS) is a rare autosomal recessive disorder presenting with poikiloderma and other clinical features, affecting the bones and eyes and, in type II RTS, presenting an increased risk for malignancy. With about 300 cases reported so far, we present a 13-year follow-up including clinical images, X-rays and genetic analysis. A 13-month-old female started with a facial rash with blisters on her cheeks and limbs at the age of 3 months along with congenital hypoplastic thumbs, frontal bossing and fine hair, eyebrows and eyelashes. The patient was lost to follow-up and returned 12 years later with palmoplantar hyperkeratotic lesions, short stature, disseminated poikiloderma and sparse scalp hair, with absence of eyelashes and eyebrows. Radiographic analysis showed radial ray defect, absence of the thumb and three wrist carpal bones, and reduced bone density. Gene sequencing for the RECQL4 helicase gene revealed a mutation on each allele. RTS is a rare disease, and in this patient we observed the evolution of her skin lesions and other clinical features, which were important for the classification of type II RTS. The next years will provide even more information on this rare disease.